International Humanitarian Law III: The 1949 Geneva Conventions and Their Additional Protocols I-III - Šmigová, Katarína (International Criminal Law, Humanitarian Law and Refugee Law From The Perspective of Human Rights Law, 2026)
This chapter examines the 1949 Geneva Conventions and their Additional Protocols as the legal framework of modern international humanitarian law (IHL). Adopted in the aftermath of the Second World War, the Geneva Conventions universalized minimum standards of humane treatment during armed conflict and expanded protection for wounded combatants, prisoners of war, and civilians. The chapter situates the Conventions and their Additional Protocols within their historical and political context, and by doing so, it highlights also the influence of earlier humanitarian instruments. A central focus of the chapter is the distinction between international and non-international armed conflicts and the legal rationale for preferring the functional concept of “armed conflict” over the politically charged term “war.” Particular attention is given to Common Article 3 of the Geneva Conventions, which establishes a minimum, non-derogable humanitarian baseline applicable to all armed conflicts and has attained customary international law status. The chapter further analyses the material scope of protection under each of the four Geneva Conventions and assesses the principal innovations introduced by Additional Protocols I and II, including the principles of distinction, proportionality, and civilian protection, as well as the regulation of means and methods of warfare. Additional Protocol III and the emblem regime are also addressed. Finally, the chapter explores the relationship between the Geneva Conventions and international human rights law and the relationship between the Geneva Conventions and international criminal law with a focus on the concept of grave breaches and their transformation into prosecutable war crimes under the Rome Statute of the International Criminal Court. By linking humanitarian obligations with individual criminal responsibility, the chapter demonstrates how the Geneva framework continues to shape accountability mechanisms and remains central to the protection of human dignity in contemporary armed conflicts. Keywords: Geneva Conventions and their Additional Protocols, international humanitarian law, armed conflict, war crimes and international criminal law